Relevansi Nilai Akuntansi Pada Saat Pengungkapan Laporan Keuangan Sebagai Pengambilan Keputusan Ekonomi - Titis Mey Rayanti; Pujiono Pujiono (Jurnal Akuntansi, 2021)
This study aims to determine the effect of financial statement disclosure that has converged IFRS with the relevance of accounting value. The objects in this study are 9 company sectors listed on the Indonesia Stock Exchange (BEI) which are classified into the Jakarta Stock Industrial Classification. The sampling method in this study used the Slovin formula in order to obtain 244 samples with a total data of 732. The technique used in this study is to use multiple linear regression analysis. The results obtained from this study state that the relevance of accounting value measured using earnings per share in financial statements that have converged IFRS is said to be increasing or having a positive effect. As for the measurement using book value per share, the result is that there is no increase when companies converge on IFRS.